2016
DOI: 10.5897/jetr2016.0593
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of energy requirements for size reduction of palm kernel and groundnut shells for downstream bioenergy generation

Abstract: The study estimated the amount of energy required for grinding palm kernel shell and groundnut shell using laboratory hammer mill and also characterize their ground physical properties. The material type and hammer mill screen aperture significantly influenced the energy requirement for grinding the two materials. For a given screen aperture size, groundnut shell consumed more energy than palm kernel shell. The energy relationship with hammer mill screen exhibited a second order polynomial form. Within the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These procedures require certain energy inputs (costs) which significantly decrease the energy and environmental balance in the entire lifecycle of the energy material (wood, grain biomass, etc.) [8][9][10][11][12][13]. According to the idea of sustainable development concerning the design of systems, devices, and processes, in three areas-the environment, society, and economy-the biomass processing lines should be characterized by the lowest possible energy consumption and environmental impact [14,15].…”
mentioning
confidence: 99%
“…These procedures require certain energy inputs (costs) which significantly decrease the energy and environmental balance in the entire lifecycle of the energy material (wood, grain biomass, etc.) [8][9][10][11][12][13]. According to the idea of sustainable development concerning the design of systems, devices, and processes, in three areas-the environment, society, and economy-the biomass processing lines should be characterized by the lowest possible energy consumption and environmental impact [14,15].…”
mentioning
confidence: 99%
“…As an interesting note, in this study, they also reported that a proportional interaction between substrate size and glucose yield has been shown, with a concurrent increase in total surface area for enzymatic degradation. 113,114 On the other hand, the application of a deep eutectic solvent, which is the high melting point emerged uid from an ionic class solvent composed of two or three components, has been demonstrated by Zulkei et al 109 As a result, the increment of 26.4% of the cellulose component in pretreated OPT as compared to untreated OPT resulted in mixed ethyl ammonium chloride and ethylene glycol. Subsequently, the highest glucose conversion achieved was 74% from the saccharication of pretreated OPT at 50 C for 24 h (celluclast 1.5 L, 50 FPU per g; Novozyme 188, 100 CBU per mL; substrate concentration, 15 mg mL À1 ).…”
Section: Enzymatic Saccharication For Biosugar Conversionmentioning
confidence: 99%
“…The parameters of the technological quasi-cutting process are influenced by many variable factors, ranging from the properties of the material to the operating parameters of the shredding unit ( Figure 12 ) [ 115 , 116 , 117 , 118 ]. The knowledge of the variables influencing the quasi-cutting process is important from the point of view of the optimal process design [ 119 ]. These factors can be classified as material, machine, and process factors.…”
Section: Development Of Shredding In Recyclingmentioning
confidence: 99%